Progress and challenge of food microbiological risk assessment in China - Li BAI; Yeru WANG; Yibaina WANG; Yan QI; Zhaoping LIU; Xin’an JIAO (Zhongguo shipin weisheng zazhi, 2020)
In the recent 10 years, China has carried out the construction of food safety risk assessment system including microbiological risk assessment (MRA) in accordance with the Food Safety Law, and has made significant progress in the work system and technical system of MRA, which has become an important basis for the risk assessment of foodborne pathogens in China. With the change of food supply chain in the global post epidemic era and the rapid development of new technologies as well as the increasing demand for the modernization of food safety management in China, it will become the main challenge for the construction of food MRA to build assessment model based on China’s dietary consumption behavior, improve the implementation ability and quality of risk assessment, and realize the application of modern technologies in risk assessment.